Self-Incompatibility Assessment of Some Italian Olive Genotypes (Olea europaea L.) and Cross-Derived Seedling Selection by SSR Markers on Seed Endosperms - Montemurro, Cinzia; Dambruoso, Giovanni; Bottalico, Giovanna; Sabetta, Wilma (Frontiers in Plant Science, 2019)
The morphology of olive flowers allows either self- or cross-pollination that could partially explain the existence of both reproductive features in this species. However, a high degree of self-incompatibility is reported for many olive genotypes, that could be an important reproductive barrier influencing olive yield. Due to the strong environmental influence, results of compatibility tests are often contradictory, making cultivar classification quite imprecise. In this study, the self-incompatibility value has been determined for four olive genotypes (Bella di Spagna, Coratina, Leccino and Ogliarola barese) widespread in the Mediterranean basin. Moreover, the incompatibility relationships of cultivar Coratina with some suitable pollinizers (Leccino, Oliastro and Picholine) have been studied in controlled crosses: the in vitro germination potential of progenies has been evaluated and the selection of cross-derived embryos has been indirectly performed by the molecular characterization of the corresponding endosperm. The results increase knowledge on factors affecting self-compatibility in olive. Moreover, they provide useful information to farmers about the most effective cultivars for the set-up of new olive grove or for graft planning. Finally, they provide a new strategy and procedure based on endosperm analysis by SSRs for an accurate, fast and relatively cheap screening of embryos/seedlings.